"We don't lie and cheat like the Collas do." Highland–lowland regionalist tensions and indigenous identity politics in Amazonian Bolivia. (December 2014) - Lopez Pila, Esther
This paper adds to the growing discussion on Bolivia's conflictive highland–lowland regionalism, going beyond it as predominantly a tension between a mestizo elite and the indigenous poor. Indigenous lowland groups' as Tacana people in the Amazon utilize their new 'indigenous identity' to effectively challenge highland indigenous migrants ( colonos ) claiming land in their region. For this they link 'being Tacana' to the lowland identity of ' Camba' . Tacana people align with lowland mestizo people participating in Camba spectacles as Beauty Contests to annunciate a common heritage. They situate themselves against highland indigenous migrants ( colonos ), an arrangement which surprises in light of the 'indigenous solidarity' propagated by the indigenous movement and indigenous President Evo Morales.